Environmental impact assessment in Namibia: the effectiveness of the system and its implementation in practice - Husselmann, Sheldon Earl (Department of Environmental and Geographical Science, 2017)
This research evaluates the effectiveness of Namibia's institutional framework for environmental impact assessment. This effectiveness evaluation consists of two parts: firstly, an evaluation of the extent to which the formal laws, regulations and procedures conform to internationally established norms for EIA systems; and secondly, an evaluation of the implementation of these formal laws, regulations and procedures in Namibian EIA practice. The research utilises a qualitative research approach, which is considered suitable for research that seeks to provide understanding with respect to 'why' and 'how' questions pertaining to policy phenomena. Several qualitative research methods were utilised including the case study method, document analysis and semi-structured interviews. Three cases from two development sectors namely, mining (two cases) and agriculture, were selected with the aid of an experienced Environmental Assessment Practitioner in order to attain the maximum information related to the focus of this research. Two sets of semi-structured interviews were conducted with 21 participants. One set was conducted with 10 individuals, including representatives from both the state and private sector, with significant experience (i.e. more than 10 years) in terms of engagement with Namibia's EIA system. Eleven interview participants, including representatives from both the state and private sector, were interviewed as part of the three selected case studies. The findings reveal that Namibia's EIA system conforms in part to internationally established norms for EIA systems in terms of the formal laws, regulations and procedures, with a few significant omissions. The findings also reveal that the implementation of these laws regulations and procedures in practice, as observed in the three selected cases, is lacking. The environmental authority lacks capacity, both in staffing and expertise. Elements of best practice on the part of proponents and their Environmental Assessment consultants were observed, however improvement in alternatives consideration and public consultation and participation is needed. The main weaknesses relate to the screening of activities that require EIA, implementation and impact monitoring and auditing, the centrality of the findings of the EIA report to decision taking, EIA system monitoring and the environmental assessment of policies, plans and programmes. To conclude, the research findings reveal that Namibia's EIA system has a significant number of weaknesses. This is however consistent with similar research conducted within a developing country context. Further research should focus on seeking to better understand the potential causes for the observed weaknesses.